Transition-Metal-Catalyzed Suzuki–Miyaura-Type Cross-Coupling Reactions of π-Activated Alcohols - Akkarasamiyo, Sunisa; Ruchirawat, Somsak; Ploypradith, Poonsaksi; Samec, Joseph S. M. (Synthesis, 2020)
The Suzuki–Miyaura reaction is one of the most powerful tools for the formation of carbon–carbon bonds in organic synthesis. The utilization of alcohols in this powerful reaction is a challenging task. This short review covers progress in the transition-metal-catalyzed Suzuki–Miyaura-type cross-coupling reaction of π-activated alcohol, such as aryl, benzylic, allylic, propargylic and allenic alcohols, between 2000 and June 2019.1 Introduction2 Suzuki–Miyaura Cross-Coupling Reactions of Aryl Alcohols2.1 One-Pot Reactions with Pre-activation of the C–O Bond2.1.1 Palladium Catalysis2.1.2 Nickel Catalysis2.2 Direct Activation of the C–O Bond2.2.1 Nickel Catalysis3 Suzuki–Miyaura-Type Cross-Coupling Reactions of Benzylic Alcohols4 Suzuki–Miyaura-Type Cross-Coupling Reactions of Allylic Alcohols4.1 Rhodium Catalysis4.2 Palladium Catalysis4.3 Nickel Catalysis4.4 Stereospecific Reactions4.5 Stereoselective Reactions4.6 Domino Reactions5 Suzuki–Miyaura-Type Cross-Coupling Reactions of Propargylic Alcohols5.1 Palladium Catalysis5.2 Rhodium Catalysis6 Suzuki–Miyaura-Type Cross-Coupling Reactions of Allenic Alcohols6.1 Palladium Catalysis6.2 Rhodium Catalysis7 Conclusions
Keywords: C–O bond activation; alcohols; cross-coupling; Suzuki–Miyaura; catalysis; green chemistry